(untitled) (SciComm Report, 2024)
Artificial intelligence (AI) is revolutionizing the way teachers design and deliver their classes, especially in creating environments that prioritize inclusion. Integrating AI into educational environments is not just about adopting new technologies; it’s about reimagining pedagogical strategies to make learning more accessible and personalized for each student. This transformation is supported by a growing body of research that highlights both the potential benefits and challenges of AI in higher education. In this review article we critically evaluate the evolving landscape of Artificial Intelligence (AI) in higher education, focusing on training methodologies and the deployment of AI tools to improve the learning process. Findings from the literature review on the integration of Artificial Intelligence (AI) in higher education suggest that the way forward requires a nuanced approach that balances innovation with ethical considerations, inclusivity and practicality.